2016
DOI: 10.1371/journal.pone.0146680
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Dorzolamide/Timolol Fixed Combination versus Latanoprost on Intraocular Pressure and Ocular Perfusion Pressure in Patients with Normal-Tension Glaucoma: A Randomized, Crossover Clinical Trial

Abstract: BackgroudTo assess the noninferiority of a dorzolamide-timolol fixed combination (DTFC) versus latanoprost in terms of intraocular pressure (IOP) and to compare blood pressure (BP), ocular perfusion pressure (OPP) and diastolic ocular perfusion pressure (DOPP) between the latanoprost and DTFC groups in patients with normal-tension glaucoma (NTG).MethodsProspective, interventional, randomized, single-blinded, crossover design study. Patients with newly diagnosed NTG that had not been treated with a glaucoma med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
1
5
0
1
Order By: Relevance
“…The most common ocular treatment-related AEs in a study comparing dorzolamide/timolol (Cosopt ® ) with P-latanoprost were eye irritation (45.5% vs. 27.3%, respectively) and ocular hyperemia (4.5% vs.18.1%, respectively). Most AEs were mild in intensity and did not lead to study discontinuation [42], in line with the results reported in the current study. The two reported AEs (eye pruritus and blurred vision) for PF-tafluprost have been reported commonly (≥1/100 to <1/10) during clinical trials for this medication [43,45].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The most common ocular treatment-related AEs in a study comparing dorzolamide/timolol (Cosopt ® ) with P-latanoprost were eye irritation (45.5% vs. 27.3%, respectively) and ocular hyperemia (4.5% vs.18.1%, respectively). Most AEs were mild in intensity and did not lead to study discontinuation [42], in line with the results reported in the current study. The two reported AEs (eye pruritus and blurred vision) for PF-tafluprost have been reported commonly (≥1/100 to <1/10) during clinical trials for this medication [43,45].…”
Section: Discussionsupporting
confidence: 92%
“…Although the rate of PRO improvement with PF-dorzolamide/timolol (35.3%) was over two-fold higher than that with P-latanoprost (16.7%), statistical significance was not reached. A double crossover study found that the IOP-lowering effect of fixed-combination dorzolamide/timolol (Cosopt ® ) was non-inferior to that of P-latanoprost in patients with glaucoma [42]. Similarly, in glaucoma patients switched to open-label PF-tafluprost, IOP was maintained at the same level as P-latanoprost [43].…”
Section: Discussionmentioning
confidence: 99%
“…DzT-FC does not exert systemic AEs and the most frequent ocular AEs are eye irritation and ocular hyperemia ( Kim et al, 2014 ; Lee et al, 2016b ; a ). PF-DzT-FC 1 improves local tolerability compared to DzT-FC ( Renieri et al, 2010 ; Shedden et al, 2010 ).…”
Section: Topical Fixed Combination Of Two Agentsmentioning
confidence: 99%
“…One study reported no effects on nocturnal IOP with topical β-antagonists in NTG eyes [ 151 ]. The effect of β-antagonist/CAI fixed combinations on diurnal IOP was reported to be similar to topical prostaglandins in NTG eyes [ 152 ]. Glaucoma filtering surgery significantly reduced the range of diurnal fluctuation [ 153 , 154 ].…”
Section: Value Of Diurnal/24-h Iop Monitoring In the Management Of Nomentioning
confidence: 99%